PENGARUH UKURAN ONGGOK TERHADAP PERTUMBUHAN TRICHODERMA SP SEBAGAI MEDIA PERTUMBUHAN AGENSIA HAYATI - Adi Prayoga; Dewi Ratih Ayu Daning (Surya Agritama : Jurnal Ilmu Pertanian dan Peternakan, 2016)
The purpose of the study is to evaluate the production of Trichoderma sp on different size of cassava bagasse. Fermentation of cassava bagasse was carried out by solid substrate fermentation method. The medium was inoculated by Trichoderma sp and incubated for ten days on different size of cassava bagasse (5, 10, and > 10 ϴ). The data were analyzed using ANOVA and the differences of the means were compared by Duncan’s new multiple range test (DMRT). The results showed that water content ( 66, 63%, 67,78%, and 68,03%) respectively.  pH of medium fermentation obtained were( 5,7, 5,58, and 5,8,) respectively and total amount of spore obtained were (13,24, 8,32, and 24,72) respectively. The production of Trichoderma sp was the best when the medium had size on >10ϴ.